A Review on Efficacy of Sensors in Capturing Biophysical Measures and its Application in the Field of Physical Therapy and Rehabilitation (Medico Legal Update, 2021)
Background: Use of sensors for assessment and treating orthopedic and neurological conditions inphysical therapy and rehabilitation is in practice since last 2 decades. Its efficiency has been promising withadvancements in research and clinical practice.Objective: The aim of the present review is to synthesize and evaluate studies which have performed a roleto test efficacy of sensors following orthopedic and neurological conditions for research and clinical practicein physical therapy and rehabilitation.Data Source: Are view of articles identified from high impact journal from Springer, Hindawi, MDPI,PLOSone, De Gruyter was performed by both researchers.Study Eligibility Criteria: Articles published only in English between January, 2010 and December, 2019were included which investigated role of sensors in physical therapy and rehabilitation.Study Appraisal and Synthesis Method: Studies were grouped as wearable, bio-mechanical pressure,motion capture sensing technology and stretch sensors.Results: From the 17 articles identified, 10 papers were involved in the review which was deemed as beingof high quality.Conclusion: Sensor technology is a full-fledged and rapidly growing field with imperative focus andnoteworthy role in assessment and treatment for upper and lower limbs insufficiencies, spinal curvecorrections in numerous orthopedic and neurological conditions. Research over the past 10 years grandlyfocused on the use of sensors in physical therapy and rehabilitation.